Pengembangan Model Pembelajaran Dengan Multimedia Dalam Pembelajaran Pencak Silat di Masa Pandemi Pada Siswa - Arief Nur Wahyudi; Abi Zahed Al Qurtubi; aba sandy prayoga (Indonesian Journal of Learning Education and Counseling, 2021)
This study aims to see the level of student learning during the Covid-19 pandemic with the background of the Covid-19 epidemic where the teaching and learning process is carried out courageously. This study aims to produce a multimedia development product for learning pencak silat, Physical Education, Sports and Health for fourth grade elementary school students. This research used a qualitative method, the data source of this research was the students of class IV SDN Wonokerto IV in the academic year 2020/2021 which were planned as many as 5 students. The data technique uses the method of observation and questionnaires to material experts, media experts and students. The results of the material expert validation were "Very Good" with a score of 4.80 and a media assessment of 4.60 in the "Good" category. The assessment of students who were tested was "Very Good" with an average score of 4.75. So it can be denied that the product developed is suitable for use in the learning process. The development of multimedia in learning pencak silat Physical education, sports and health can increase student motivation and learning outcomes during the Covid-19 pandemic in grade IV of Wonokerto IV State Elementary School.